Location of the internal carotid artery and ophthalmic artery segments for non-invasive intracranial pressure measurement by multi-depth TCD. Issue 1 (1st January 2017) - Hamarat, Yasin; Deimantavicius, Mantas; Kalvaitis, Evaldas; Siaudvytyte, Lina; Januleviciene, Ingrida; Zakelis, Rolandas; Bartusis, Laimonas
ABSTRACT: The aim of the present study was to locate the ophthalmic artery by using the edge of the internal carotid artery (ICA) as the reference depth to perform a reliable non-invasive intracranial pressure measurement via a multi-depth transcranial Doppler device and to then determine the positions and angles of an ultrasonic transducer (UT) on the closed eyelid in the case of located segments. High tension glaucoma (HTG) patients and healthy volunteers (HVs) undergoing non-invasive intracranial pressure measurement were selected for this prospective study. The depth of the edge of the ICA was identified, followed by a selection of the depths of the IOA and EOA segments. The positions and angles of the UT on the closed eyelid were measured. The mean depth of the identified ICA edge for HTG patients was 64.3 mm and was 63.0 mm for HVs ( p = 0.21). The mean depth of the selected IOA segment for HTG patients was 59.2 mm and 59.3 mm for HVs ( p = 0.91). The mean depth of the selected EOA segment for HTG patients was 48.5 mm and 49.8 mm for HVs ( p = 0.14). The difference in the located depths of the segments between groups was not statistically significant. The results showed a significant difference in the measured UT angles in the case of the identified edge of the ICA and selected ophthalmic artery segments ( p = 0.0002). We demonstrated that locating the IOA and EOA segments can be achieved using the edge of the ICA as a reference point. Abbreviations : OA: ophthalmic artery; IOA: intracranial segments of the ophthalmic artery; EOA: extracranial segments of the ophthalmic artery; ICA: internal carotid artery; UT: ultrasonic transducer; HTG: high tension glaucoma; SD: standard deviation; ICP: intracranial pressure; TCD: transcranial Doppler